(untitled) (Journal of Geography and Environmental Management, 2016)
Problems of using nature-recreational resources of Kyrgyzstan, development mountain tourism, potential of mountain tourism, recreational resources and recreational regional prediction and strategy of development the tourism branch of the Kyrgyz Republic.